Strategi Advokasi Bagi Korban KDRT Dalam Memperjuangkan Hak Asus Anak Pasca Perceraian - Azima Amalia; Bella Asri Pratiwi; Maskana Qurrota Ayyun; M.Ravi Al-Muntashir; M. Natsir Asnawi; Wagianto (An Natiq, 2026)
Divorce resulting from domestic violence (KDRT) raises complex legal issues in determining child custody (hadhanah), particularly when normative legal provisions intersect with the need to ensure effective protection for both children and victims of violence. In the practice of Religious Courts, custody decisions are not solely based on textual legal provisions but also take into account the child's safety, welfare, and best interests. This article aims to analyze the normative construction of child custody following divorce caused by domestic violence from the perspective of Islamic Family Law and to formulate advocacy strategies that strengthen the substantive protection of children's custodial rights. This study employs normative legal research using statutory, conceptual, and case approaches through a library-based examination of legislation, the Compilation of Islamic Law, Religious Court decisions, and relevant academic literature. The findings indicate that although custody of children who have not yet reached the age of discernment (mumayyiz) is generally granted to the mother, judges may depart from this principle in cases involving domestic violence when such a decision is necessary to ensure the child's safety and best interests. The study further finds that effective advocacy requires strengthening legal arguments based on victim protection, comprehensive evidence of the impact of domestic violence on children, and the consistent application of the best interests of the child principle. Therefore, the principles of best interests of the child and maslahah al-thifl should serve as the primary foundation for hadhanah decisions. The harmonization of Islamic law and Indonesian positive law provides a stronger framework for protecting both children and victims of domestic violence while promoting substantive justice in child custody disputes.